Women and Media: Libyan Female Journalists from Gaddafi Media to Post‐ revolution: Case Study. Issue 1 (31st December 2020) - El Issawi, Fatima
Abstract: his article examines the representation of women in Libyan national traditional media before, during and after the February 2011 revolution that led to the overthrow of the Gaddafi regime. What roles did female journalists assume within national traditional newsrooms and how did these roles evolve from activism in the defense of women's causes and the official revolutionary ideals of the former regime to spreading the message of the revolutionaries during the uprising? This article further reflects on changes in the nature of female journalists' roles in the new post-revolution media landscape. The opening of the media market to private ownership for the first time in Libya's history is accompanied by an expansion of women's presence in Libyan newsrooms, where this increased visibility is to be viewed primarily as a mean of attracting audiences. In the shaky media landscape that characterizes the post-revolutionary period, this expansion reflects the clash between the conservative values of Libyan society and the liberal values of the open market. I argue that the growing number of women in national Libyan media post-revolution is not reflective of a general trend towards women's empowerment in a country struggling with the spread of violence and the legacy of the past. Rather, the thorny process of restructuring national media post-revolution and the need for new media outlets capable of catering for large audiences are empowering the presence of women in newsrooms as a strong marketing asset.